Burn camps for burns survivors—Realising the benefits for early adjustment: A systematic review. Issue 1 (February 2020) - Kornhaber, Rachel; Visentin, Denis; Kaji Thapa, Deependra; West, Sancia; Haik, Josef; Cleary, Michelle
Highlights: Children, parents and staff have consistent perceived benefits of camp attendance. Qualitative data supports the applicability of burn camps in improving the psychosocial outcomes for children with burn injuries. Quantitative data does not demonstrate consistent, long-lasting benefits. The findings should lead to further research to explain the gap between quantitative and qualitative outcomes. Abstract: Objectives: Child and adolescent burn survivors benefit from skills to cope with the physical and mental challenges associated with their injuries. Burn camps can offer an opportunity to build these skills. In this study, we systematically review the best available evidence on burn camps in order to better assess their impact on burn survivors. Method: A systematic review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines. A total of 815 articles on recreational therapeutic camps for burn survivors were retrieved from PubMed, PsycINFO, CINAHL and Scopus restricted to the English language and published before or by May 2018. Critical Appraisal Skills Programme (CASP) for Qualitative Studies Checklist and the Joanna Briggs Institute (JBI) Critical Appraisal Checklist for non-randomized experimental studies were used to assess the methodological rigour of the quantitative studies. Results: Quantitative data did not support any long-lasting impacts on psychosocial wellbeing. Qualitative data showed children, parents and staff all perceived benefits from camp attendance, including companionship and belonging. Conclusion: Further research is required to understand the lack on congruence between qualitative and quantitative data. Qualitative data suggests burn camps are beneficial for children with burn injuries.